ANALISIS YURIDIS SURAT SERUAN GUBERNUR NOMOR 8 TAHUN 2021 TENTANG PEMBINAAN KAWASAN DILARANG MEROKOK - Geofani Milthree Saragih (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2022)
This study aims to analyze the legal position of the Governor's Letter of Appeal Number 8 of 2021 concerning the Development of a No Smoking Area associated with the rights of cigarette sellers and users. This research is a type of descriptive research using a qualitative approach. The technique used to collect data using observation, literature study and tracing and archives. The results show that the Governor's Letter of Appeal Number 8 of 2021 concerning the Development of a No Smoking Area has ambiguity in its regulation in positive law in Indonesia, both from legal sources that are followed up, the substance and who signed the Governor's Appeal do not have certainty. If the Governor's Letter of Appeal Number 8 of 2021 concerning the Development of a No Smoking Area is discretionary, then it is not in accordance with AUPB. The application of the Governor's Letter of Appeal Number 8 of 2021 concerning the Development of a No Smoking Area is contrary to the Decision of the Constitutional Court Number 6/PUU-VII/2009 and the Constitutional Court Number 57/PUU-IX/2011. Then, with the issuance of the Governor's Letter of Appeal Number 8 of 2021 concerning the Development of No Smoking Areas, it has caused losses for cigarette sellers and cigarette users, not only in Jakarta, but also outside Jakarta. In practice, legal products in the form of a Governor's Letter of Appeal are only found in Jakarta. It is hoped that in the future there will be a clear setting of boundaries regarding the formation of the Governor's Letter of Appeal.